THE EFFECT ROLL ROAD OF ROUGHNESS ON THE PERFORMANCE OF NUTMEG - Husnul Khotimah; Anas Muhktar; Rubiono, Gatut (Fakultas Teknik Universitas PGRI Banyuwangi, 2022)
The process of flattening nutmeg is one of the steps that must be carried out before it becomes a dish that can be enjoyed or marketed. The dimensions of the fruit and the relatively unequal surface structure between each other can hinder the flattening process if done in a conventional way. The addition of a profile to increase the surface roughness on the rollers of the flattening machine will affect the performance of the flattening process using a contra-rotary roll type flatter machine. The purpose of this study was to determine the effect of adding a surface profile to increase roller roughness on the flattening performance of nutmeg. The research was conducted by experiment where the profile was made with a pattern of transverse grooves on the rollers using variations in the number of grooves including 4; 6; and 8. Machine performance analysis includes the duration of the flattening process and the physical characteristics of the fruit being processed. The results showed that the maximum weight difference occurred in the 6 groove roller variation of 4.8 g with the highest thickness difference in the 6 groove variation of 3.35 mm. The fastest duration is shown in groove 8 variation of 1.98 sec. The lowest use of electric power is found in the variation of the 8 roller groove of 35.64 W.